Futuristic Visions and Classical Myths: Nonlinear Time as a Device for Reinterpreting Antique Plots in Dan Simmons’ Novel “Ilium” - Mariia Iliuchenko (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
Ancient mythology remains an important source of inspiration for contemporary literature, where its plots and images are used to reinterpret universal questions of human existence. In the context of postmodern and metamodern paradigms prioritizing non-linearity, intertextuality, and multi-layered narratives, mythology becomes a tool for examining such fundamental themes as time, space, and fate. The works of Dan Simmons, in particular his Trojan Dylogy, are relevant for study due to the combination of ancient stories with science fiction and the question of the relationship between the past, future and present.